Postoperative Functional Assessment in Patients with Tumors Around the Knee Treated with Endoprosthetic Reconstruction: A Multicenter Retrospective Cohort Study - Yun-long Zhao MD; Hao-ran Zhang MD; Jing-yu Zhang MD; Yong-cheng Hu MD, PhD (Technology in Cancer Research & Treatment, 2023)
Objectives The restoration of as much normal function as possible has become an important goal following the endoprosthetic reconstruction. The objective of this study was to assess the functional outcome after endoprosthetic reconstruction for tumors around the knee and to explore prognostic factors of functional outcome. Methods We retrospectively collected data on patients who underwent tumor prosthetic replacements consecutively. Musculoskeletal Tumour Society score and Toronto Extremity Salvage Score were used to assess the functional outcome at 1, 3, 6, 12, and 24 months after surgery. The logistic model was used to select factors that had potential predictive value for postoperative function. Potential prognostic factors included age, gender, tumor site, type of tumor, length of bone resection, type of prosthesis, length of prosthetic stem, chemotherapy, pathological fracture, and body mass index. Results At the 24 months after surgery, the mean musculoskeletal tumor society (MSTS) score was 81.4% and the mean Toronto extremity salvage score (TESS) was 83.6%. At the last follow-up, 68% of patients and 73% of patients received perfect or good MSTS score and TESS score, respectively. The multivariate analysis according to ordered-logit model showed that age < 35 years, distal femoral prosthesis, and length of bone resection < 14 cm were independent prognostic factors of better functional outcome. Conclusions Endoprosthetic reconstruction may provide good functional results for most patients. Younger patients with distal femoral prosthesis and shorter resection of bone (on the premise of complete resection of tumor) are more likely to obtain satisfactory functional results after surgery.